P3.164 Antibiotic resistance and molecular typing of neisseria gonorrhoeae isolated from the three overseas sites through the global emerging infections surveillance and response system (GEIS). (8th July 2017) - Rahman, Nazia; Kluz, Nicole; Puplampu-Attram, Naiki; Letizia, Andrew; Montano, Silvia; Regeimbal, James; Mccoy, Andrea; Akhvlediani, Tamar; Washington, Michael; Soge, Olusegun; Macalino, Grace; Jerse, Ann
Abstract : Introduction: Increasing antibiotic resistance in Neisseria gonorrhoeae (GC) threatens treatment and control measures for gonorrhoea and can affect military readiness. The Global Emerging Infectious Surveillance and Response System of the US Armed Forces Health Surveillance Branch supports a repository for GC isolated at US military treatment facilities in the continental US (CONUS) and at several overseas (OCONUS) labs. Here we report the antibiotic susceptibility and N. gonorrhoeae multi-antigen sequence types (NG-MAST) of isolates collected from three OCONUS sites: Republic of Georgia, Peru and Ghana in 2012–2016. Methods: GC was identified using standard biochemical and serological methods. Susceptibility to ceftriaxone, cefixime (Cfx), azithromycin (Az), gentamicin, penicillin (Pen), tetracycline (Tet), ciprofloxacin (Cip), and spectinomycin was determined by Etest. β-lactamase (ßL) activity was determined by nitrocefin hydrolysis. NG-MAST was performed using standard methods. Results: Fifty-seven confirmed GC isolates were obtained from the three OCONUS sites. Cip resistance occurred in 74% (Ghana) and 89% (Peru) of isolates, with 63.2% (Ghana) and 28.6% (Peru) of isolates Cip R, Pen R and Tet R . Two isolates with reduced susceptibility to Cfx were identified among isolates from Ghana and Georgia and 18 isolates with reduced susceptibility to Az were identified across the 3 sites. Over 65% of isolates from Ghana and Peru produced ßL. Cip R strains primarily encoded S91, D95A or S91F, D95G substitutions in GyrA, combined with S87R (Peru) or S87N (Ghana) substitutions in ParC. Interestingly, a high proportion of isolates from Ghana (36.8%) and Peru (85.7%) were of unique NG-MAST types. Conclusion: Multidrug resistant GC and ßL production are common in these OCONUS sites. Several previously undescribed NG-MAST sequence types were identified in Peru and Ghana, suggesting the GC strains circulating in these countries are different from those in North America, Australia, and Europe. Further surveillance is needed to inform treatment recommendations in OCONUS sites.